2016
DOI: 10.1016/j.jcmg.2015.11.011
|View full text |Cite|
|
Sign up to set email alerts
|

Noninvasive Cardiovascular Risk Assessment of the Asymptomatic Diabetic Patient

Abstract: Increased cardiovascular morbidity and mortality in patients with type 2 diabetes is well established; diabetes is associated with at least a 2-fold increased risk of coronary heart disease. Approximately two-thirds of deaths among persons with diabetes are related to cardiovascular disease. Previously, diabetes was regarded as a “coronary risk equivalent,” implying a high 10-year cardiovascular risk for every diabetes patient. Following the original study by Haffner et al., multiple studies from different coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 152 publications
0
52
0
3
Order By: Relevance
“…Recent studies have shown that MiVD in patients with T2D and diagnosed HFpEF is highly prevalent and associated with HF severity and worse outcome; however, ours is the first to show the independent prognostic association between MiVD and development of HFpEF. Echocardiographic studies have shown that T2D is associated with abnormalities of diastolic function independent of the presence of coronary artery disease . In addition, the presence of MiVD in patients with T2D also seems to be associated with the presence of diastolic dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that MiVD in patients with T2D and diagnosed HFpEF is highly prevalent and associated with HF severity and worse outcome; however, ours is the first to show the independent prognostic association between MiVD and development of HFpEF. Echocardiographic studies have shown that T2D is associated with abnormalities of diastolic function independent of the presence of coronary artery disease . In addition, the presence of MiVD in patients with T2D also seems to be associated with the presence of diastolic dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…39 In addition, the Imaging Council of the American College of Cardiology recently concluded that CAC screening is the most sensitive noninvasive risk stratification tool among asymptomatic persons with diabetes. 40 Although screening for CHD in patients with diabetes has previously been found to not be of benefit in reducing CHD and ASCVD events, 41,42 other reports 4345 have found that patient awareness of an abnormal CAC score and coronary CT angiography results is associated with increased adherence to preventive therapies, lifestyle changes, and improvement in lipid levels and other risk factors, suggesting that CAC screening might help to support behavioral modification. In addition, Nasir et al 46 found that CAC screening in MESA participants without diabetes can help identify those at adequately high risk who would benefit from statin therapy (and those at low risk who would not benefit).…”
Section: Discussionmentioning
confidence: 99%
“…Its ability to visualise the coronary arteries, typically measuring 3–4 mm in diameter, stems from its high spatial resolution 25 26. CTCA is primarily used to assess patients with low to intermediate pretest probability of significant coronary artery disease,27 but could potentially be used in the CV risk assessment of patients with RA.…”
Section: Imaging Modalitiesmentioning
confidence: 99%